Sociodemographic and behavioral factors associated with controlled hypertension after 9 years of observation of a PURE Poland cohort study - Zatońska, Katarzyna; Basiak-Rasała, Alicja; Połtyn-Zaradna, Katarzyna; Gaweł-Dąbrowska, Dagmara; Wołyniec, Maria; Karczewski, Maciej; Szuba, Andrzej (Frontiers in Public Health, 2023)
Introduction Despite some improvement in awareness and treatment of hypertension, blood pressure control is still below expectations in Poland. The aim of the study was to analyze the secular trend of hypertension prevalence in the PURE Poland cohort study over 9 years of observation and to analyze factors associated with controlled HT. Methods The study group consisted of 1,598 participants enrolled in a Prospective Urban and Rural Epidemiological Study (PURE), who participated both in baseline (2007–2010) and 9-year follow-up (2016–2019). Hypertension was ascertained on the basis of (1) self-reported hypertension previously diagnosed by the physician, (2) self-reported anti-hypertensive medication, and/or (3) an average of two blood pressure measurements ≥140 mmHg systolic BP and/or ≥90 mmHg diastolic BP. Results The prevalence of hypertension increased from 69.4% at baseline to 85.9% at 9-year follow-up. The chance of HT was 8.6-fold higher in the oldest vs. the youngest age group [OR 8.55; CI 4.47–16.1]. Male sex increased the chance for hypertension over 3-fold [OR 3.23; CI 2.26–4.73]. Obesity, according to BMI, increased the chance of HT 8-fold [OR 8.01; CI 5.20–12.8] in comparison with normal body weight. Male sex decreased the chance of controlled HT after 9 years [OR 0.68; CI 0.50–0.92]. There was no statistically significant association between controlled HT and age or place of residence. Higher and secondary education increased the chance of controlled HT over 2-fold in comparison with primary education [OR 2.35; CI 1.27–4.34, OR 2.34; CI 1.33–4.11]. Obesity significantly decreased the chance of controlled HT after 9 years in comparison with normal body weight [OR 0.54; CI 0.35–0.83]. Conclusion Factors significantly increasing the chance for controlled hypertension after 9 years were female sex, secondary and tertiary education, normal body weight, and avoiding alcohol drinking. Changes in lifestyle, with special emphasis on maintaining normal body weight, should be the basis of prevention and control of HT.